Frequency optimization in the eddy current test for high purity niobium. Issue 1 (2nd January 2017) - Joung, Mijoung; Jung, Yoochul; Kim, Hyungjin
Abstract: The eddy current test (ECT) is frequently used as a non-destructive method to check for the defects of high purity niobium (RRR300, Residual Resistivity Ratio) in a superconducting radio frequency (SRF) cavity. Determining an optimal frequency corresponding to specific material properties and probe specification is a very important step. The ECT experiments for high purity Nb were performed to determine the optimal frequency using the standard sample of high purity Nb having artificial defects. The target depth was considered with the treatment step that the niobium receives as the SRF cavity material. The results were analysed via the selectivity that led to a specific result, depending on the size of the defects. According to the results, the optimal frequency was determined to be 200 kHz, and a few features of the ECT for the high purity Nb were observed.